GAMBARAN FAKTOR TERHAMBATNYA PELAKSANAAN ANALISIS BERKAS REKAM MEDIS RAWAT INAP DI RS AKADEMIK UGM - Rustiyanto, Ery; Akhsani, Fathiya; Azizah, Qisti Nur (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2026)
Background: Medical record quality assurance is one of the implementations. Efforts to maintain the quality of these records include analyzing inpatient medical records at the Gadjah Mada University (UGM) Academic Hospital. The analysis of inpatient medical records at the Gadjah Mada University (UGM) Academic Hospital is carried out by two people, with an average of 1,680 inpatients per month in 2024. Observations at the analyst's workplace reveal a significant accumulation of unanalyzed medical records. This accumulation of medical records disrupts other processes, such as the difficulty of locating inpatient records for patients who wish to borrow them, either by staff or for research purposes. Medical record analysis is performed on paper/manual medical records, and some have switched to electronic medical records. This is quite time-consuming for staff, as they must consult both manual and electronic medical records. Meanwhile, based on the trend in the number of inpatient visits during 2024, it is predicted that in 2025 the number of inpatient visits will increase to around 2,000 patients or even more per month. Objective: To identify factors hindering the analysis of inpatient medical records at the Gadjah Mada University (UGM) Academic Hospital. Research Method: This study used a descriptive design with a qualitative approach to identify factors hindering the implementation of inpatient medical record analysis at the Gadjah Mada University (UGM) Academic Hospital, using Fishbone analysis.